Current Novel Advances in Bronchoscopy - Jiang, Jeffrey; Chang, Stephanie H.; Kent, Amie J.; Geraci, Travis C.; Cerfolio, Robert J. (Frontiers in Surgery, 2020)
Screening for lung cancer has changed substantially in the past decade since The National Lung Screening Trial. The resultant increased discovery of incidental pulmonary nodules has led to a growth in the number of lesions requiring tissue diagnosis. Bronchoscopy is one main modality used to sample lesions, but peripheral lesions remain challenging for bronchoscopic biopsy. Alternatives have included transthoracic biopsy or operative biopsy, which are more invasive and have a higher morbidity than bronchoscopy. In hopes of developing less invasive diagnostic techniques, technologies have come to assist the bronchoscopist in reaching the outer edges of the lung. Navigational bronchoscopy is able to virtually map the lung and direct the biopsy needle where the scope cannot reach. Robotic bronchoscopy platforms have been developed to provide stability and smaller optics to drive deeper into the bronchial tree. While these new systems have not yet proven better outcomes, they may reduce the need for invasive procedures and be valuable armamentarium in diagnosing and treating lung nodules, especially in the periphery.